2009
DOI: 10.1007/s00438-009-0487-x
|View full text |Cite
|
Sign up to set email alerts
|

Modular architecture and evolution of the map-1 gene family in the root-knot nematode Meloidogyne incognita

Abstract: In eukaryotes, repeat proteins (i.e. proteins that contain a tandem arrangement of repeated structural elements) are often considered as an extra source of variability, and gains and losses of repeats may be an important force driving the evolution and diversification of such proteins, that could allow fast adaptation to new environments. Here, we report genomic sequences of the MAP-1 protein family from of the asexual, plant-parasitic nematode Meloidogyne incognita. The encoded proteins exhibited highly conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 33 publications
2
40
0
2
Order By: Relevance
“…For example, M. incognita secreted map-1.2 protein shows specifically increased expression in Mi-1 resistant tomato lines. It suggests that the map-1.2 might be a putative avirulent (Avr gene) response to Mi gene (Castagnone-Sereno et al, 2009). A similar effect has been shown for H. glycines chorismate mutase (Hg-cm-1) in soybean cultivars.…”
Section: Parasitomes/secretomes and Parasitism Genes Of The Nematodessupporting
confidence: 63%
See 1 more Smart Citation
“…For example, M. incognita secreted map-1.2 protein shows specifically increased expression in Mi-1 resistant tomato lines. It suggests that the map-1.2 might be a putative avirulent (Avr gene) response to Mi gene (Castagnone-Sereno et al, 2009). A similar effect has been shown for H. glycines chorismate mutase (Hg-cm-1) in soybean cultivars.…”
Section: Parasitomes/secretomes and Parasitism Genes Of The Nematodessupporting
confidence: 63%
“…A similar effect has been shown for H. glycines chorismate mutase (Hg-cm-1) in soybean cultivars. But still the plant targets for both these Avr candidate genes and their particular function are unknown (Bekal et al, 2003;Lambert et al, 2005;Castagnone-Sereno et al, 2009). However, another M. incognita gene, Cg-1, was confirmed as an Avr gene corresponding to the Mi-1 resistance gene in tomato (Gleason et al, 2008).…”
Section: Parasitomes/secretomes and Parasitism Genes Of The Nematodesmentioning
confidence: 99%
“…MAP-1 is a protein (whose sequence is characterised by internal repetitive motifs of 13 and 58 amino acids) secreted from the amphids in avirulent populations of M. incognita (Semblat et al, 2001). Map-1 belongs to a small gene family, specific to RKNs and only found in avirulent lines of the three Meloidogyne species that are controlled by the tomato resistance gene Mi-1 (Castagnone-Sereno et al, 2009;Semblat et al, 2001). It has been suggested that MAP-1 could be involved in early recognition steps mediated by Mi-1 and that the specificity of the plant-nematode interaction could be related to the variation in the number or arrangement of repeats in the proteins.…”
Section: Proteins Of Unconfirmed Function In Parasitismmentioning
confidence: 99%
“…2A). The best example is MAP-1, RKN effector proteins which were identified in near-isogenic lines of M. incognita selected on plants carrying Mi-1 resistance gene (Semblat et al 2001), and subsequently, showed correlation to nematode avirulence (Castagnone-Sereno et al 2009), indicating ETI response in association with the R-gene Mi-1 (Fig. 2A).…”
Section: Co-evolution Of R-and Avr-genementioning
confidence: 99%